GOOGLE CLASSROOM LMS DEVELOPMENT TO IMPROVE EMPLOYEES' SOFTSKILLS AND TECHNICAL SKILLS - Rasyid, Intan Nur Ilhami (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
The development of human resources in the poultry industry poses unique challenges, particularly in enhancing employees’ soft and technical skills. Limited access to flexible and relevant training demands an innovative technology-based solution. This community service activity aimed to design and implement a Google Classroom-based Learning Management System (LMS) as a training platform for employees at a poultry company in West Java. The implementation stages included needs assessment, training module design, LMS deployment, and evaluation through pre-test and post-test. The results showed significant improvement in communication, Google Workspace proficiency, and digital reporting autonomy. Google Classroom proved to provide accessible learning, improve interaction, and foster a tech-based working culture. Despite technical barriers for some participants, this activity demonstrated that LMS-based training is effective beyond educational settings. These findings emphasize the importance of developing digital learning models to support productivity and workforce competitiveness in the poultry industry.